MODEL MANAJEMEN MUTU MADRASAH KAJIAN DI MIN & MI MA’RIF PAGERAJI PURWOKERTO - Rohmat Rohmat (Jurnal Penelitian Agama, 2018)
Abstract: The quality of madrasah education needs to get serious attention both from process aspect and its result. The quality of madrasah education is also influenced by the family and community environment. This brings with it the need for a review and mapping of the quality management model of education in Madrasah Ibtidaiyah. The Madrasah Ibtidaiyah of Purwokerto and MI Ma'arif Pageraji Purwokerto were chosen to be the subject of this study with the consideration that the school has a good quality management system. This study aims to find the typology of quality management education in MI that is effective so that it can be replicated. Based on the findings of the data, it can be concluded as follows: (1) Quality planning conducted in MIN and MI Ma’arif pageraji Purwokerto through (a) improvement of teacher competence, through OJT activity (on the job trainning), (b) teacher. (c) Development of natural competence matrix. (d) Parent and community cooperation in establishing some madrasah programs. (2) Quality control system conducted in MIN and MI Ma’arif pageraji Purwokerto done through supervision activities. (3) Quality assurance conducted in MIN and MI Ma’arif pageraji Purwokerto done internally by madrasah and audited through accreditation activities run by the accreditation bodies of madrasah or other institutions externally. Keywords: Management model, quality of madrasah.